2018
DOI: 10.1007/s40618-018-0917-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating insulin-like peptide 5 levels and its association with metabolic and hormonal parameters in women with polycystic ovary syndrome

Abstract: PCOS subjects exhibited an elevation in circulating INSL5 levels along with a link between INSL5 level induction and metabolic-hormonal parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
9
2
Order By: Relevance
“…Primary tissues of expression for Insl5 are the L-cells of the distal colon, hypothalamus, kidney, thymus and reproductive tissues; while Rxfp4 is expressed in the colon and subtending vagus nerve efferents, as well as in the cerebellum, reproductive tissues and kidney: ( 4 , 5 ) GTEX consortium). Collectively these tissues of expression correlate well with current hypotheses that INSL5 a) is a gut hormone that modulates glucose metabolism either directly or indirectly via gluconeogenesis ( 6 8 ); b) is an orexigenic hormone that influences satiety, through both gut-nervous system and hypothalamus-cerebellum cross-talk with RXFP4 ( 9 ); c) plays roles in female and male fertility ( 6 , 10 , 11 ), and d) together with RXFP4, are markers of colorectal and breast cancer progression ( 12 15 ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Primary tissues of expression for Insl5 are the L-cells of the distal colon, hypothalamus, kidney, thymus and reproductive tissues; while Rxfp4 is expressed in the colon and subtending vagus nerve efferents, as well as in the cerebellum, reproductive tissues and kidney: ( 4 , 5 ) GTEX consortium). Collectively these tissues of expression correlate well with current hypotheses that INSL5 a) is a gut hormone that modulates glucose metabolism either directly or indirectly via gluconeogenesis ( 6 8 ); b) is an orexigenic hormone that influences satiety, through both gut-nervous system and hypothalamus-cerebellum cross-talk with RXFP4 ( 9 ); c) plays roles in female and male fertility ( 6 , 10 , 11 ), and d) together with RXFP4, are markers of colorectal and breast cancer progression ( 12 15 ).…”
Section: Introductionsupporting
confidence: 81%
“…Retrieval of the RNA-seq data at the EMBL-EBI expression atlas ( ), last accessed May 2019) uncovered 26 experiments for Insl5 and 25 for Rxfp4 in which significant differences were observed between treatment arms: five of these studies found decreased expression of Insl5 or Rxfp4 in association with metabolic disorders such as Crohn’s disease, while 22 (11- Insl5 , 11- Rxfp4 ) found significant changes in gene expression associated with various cancer including colon and breast (summarized in Table S3 ). Further, a clinical study in humans undergoing bariatric surgery found that plasma levels of INSL5 were inversely correlated with C-reactive protein (CRP), a marker of inflammation secreted by the liver into plasma in response to acute stress ( 16 ), and positively correlated with BMI and insulin resistance ( 11 , 16 ). Taken together with the results presented here, we propose that INSL5 and RXFP4 play roles in immune system signaling, both in the central and peripheral immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic elevation of INSL5, which may contribute to a chronic increase in GLP-1 secretion, could lead to sustained insulin secretion (Luo et al 2015). Although the assays for INSL5 remain to be fully reliable (Kay et al 2017), Bicer et al (2019) proposed that PCOS patients develop higher levels of circulating INSL5, which in turn may contribute to the development of insulin resistance and metabolic syndrome (Bicer et al 2019).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…INSL5 has been reported to (1) modulate glucose homeostasis (Burnicka-Turek et al 2012, Luo et al 2015, Lee et al 2016, Ang et al 2017; (2) act as an orexigenic hormone (Grosse et al 2014, Li et al 2020); (3) play a role in both male and female fertility (Burnicka-Turek et al 2012, Wagner et al 2016, Yeganeh et al 2017, Bicer et al 2019; (4) be a marker of colorectal endocrine cells, neuroendocrine tumors, and breast cancer (Mashima et al 2013, Thanasupawat et al 2013, Lee et al 2016, Sun et al 2019; (5) regulate metabolic reprogramming and act as a potential diagnostic, prognostic, and therapeutic target of nasopharyngeal carcinoma (Li et al 2020); (6) play a role in immune response (Vahkal et al 2021); (7) stimulate colorectal propulsion (Diwakarla et al 2020, Pustovit et al 2021; and (8) based on evidence available from our previous studies and the work of others, we propose a novel function that INSL5-RXFP4 may modulate responses to the gut microbiome (Wichmann et al 2013, Lee et al 2016, Alnafea et al 2019, Hecker et al 2019, Vahkal et al 2021. Some studies have suggested that since measurable effects of INSL5 are low within animal models, the physiological role of INSL5 may be less relevant than other gut hormones (Ang et al 2018, Lewis et al 2020; however, further research is necessary to fully understand the physiological role(s) of the pair in humans.…”
Section: Introduction: Insl5-rxfp4mentioning
confidence: 99%
See 1 more Smart Citation